The Erie Canal - Spier, Peter; Allen, Thomas S. ([New York : Children's Choice Book Club)
The folk song describing the journey from Albany to Buffalo on the Erie Canal in the 1850's. Includes musical notation.
Originally published: Garden City, N.Y. : Doubleday, 1970.
The illustrations are accompanied by the words of the song "Low bridge! Everybody down" by Thomas S. Allen.
Keywords: Folk songs -- United States -- Texts; Folk songs -- United States